Konseling Kelompok Dengan Teknik Expressive Writing Therapy Untuk Meningkatkan Penerimaan Diri Siswa Broken Home - Kristiani, Oktrie; Karuniaty Sangalang, Oktamia; Feronika, Nopi (Universitas Palangka Raya, 2025)
Self-acceptance is a person's level of awareness about his or her personal traits and the desire to accept his or her circumstances. Self-acceptance is an attitude that basically feels satisfied with oneself, recognizes the qualities and talents possessed, and realizes the shortcomings in oneself. The purpose of this study was to determine the application of group counseling with expressive writing therapy techniques to increase self-acceptance in students who are victims of broken homes at SMK Negeri 1 Palangka Raya. This type of research is experimental quantitative research, pre-experimental designs in the form of one group pretest-posttest design. The population in this study were students in class XI TKR and XI TAV, a sample of 4 students with purposive sampling technique. Data collection techniques using, questionnaires, observation, interviews, and documentation. Data were analyzed using t-test with the help of SPSS 25 for windows. Based on the results of the study, it is known that there are 3 students with low category self-acceptance and 1 student in the medium category, with an average pre-test score of 91 in the low category. After getting group counseling services, it shows that the post-test results increase with an average post-test score of 101 in the moderate category. Then the t-test was carried out and the t-count> t-table value was obtained = 10.088> 3.182 so that H0 was rejected and Ha was accepted, meaning that it could be concluded that there was an increase in self-acceptance in students who were victims of broken homes after being given group counseling services with expressive writing therapy techniques.